INFLUENCE OF TECHNOLOGY MODERNIZATION OF TAXATION ADMINISTRATION AND SOCIALIZATION OF TAXATION ON TAXPAYER COMPLIANCE (Case Study at KPP Pratama Bandung Cibeunying) - Raihan, Diva Aulia; Damara, Shandy; Nurlaily, Sherlina Mauldy; Aprilia, Putri Ayu; Fahm, Rindhu Rosyada; Arwaty, Dini (CENTRAL ASIA AND THE CAUCASUS, 2022)
This research aims to : 1) See the impact of modern technology on tax administration and tax socialization on taxpayer compliance. 2) Know what impact tax socialization has on taxpayer compliance. The research site was conducted at the Office of Tax Services (KPP) Pratama Bandung Cibeunying. The independent variable in the study is the impact of the technology used to modernize the tax administration, while the dependent variable is personal compliance by taxpayers. The method used in this study is an explanatory method with a survey approach. In this study, the population used is a taxpayer who is registered with the Pratama Bandung Cibeunying Tax Services Office (KPP). The type of data used in this research is quantitative. Data were collected using questionnaire techniques. The number of samples in this study was 30 respondents. Sampling is done by purposive sampling method. The data analysis methods used by researchers are multiple linear regression analysis, validity test, rehabilitation test, classical assumption test, coefficient of determination (R2 test), f test and t test. From the results of the investigation it appears that the modernization technology of the tax administration has no effect on the compliance of the taxpayers in the Pratama Bandung Cibeunying Tax Services Office (KPP). While tax socialization affects taxpayer compliance in the Pratama Bandung Cibeunying Office of Tax Services (KPP).